La “unión de todos”: teatro y discurso político en la independencia, Lima 1820-21 - Cosamalón Aguilar, Jesús A. (1996)
The article attempts to track political debate as it occurred during the days of Peru's Independence, using a source that has been analyzed relatively little in Peruvian history. The theater, beyond its formal or artistic, representations, provides a unique perspective on the concerns and tensions affecting society, especial/y against a backdrop of political revolt. The city of Lima, the final scenario of the freedom movement was a stage for political debate between monarchists and republicans. The proposals of the day needed a public space where a crowd could gather and messages be transmitted lo the elite and society at large. The theater served this purpose during tire stormy years of the Independence. This analysis, therefore, concentrates on political proposals presented in plays, fully aware that it ignores other viewpoints. What we find is the freedom movement's message molded to the schemes and needs of the Lima elite. From that point of view, political discourse tended more toward a continuation of the colonial system rather than radical change. Furthermore, the elite had put up with several social reforms in recent decades and, with the memory of Tupac Amaru still fresh, would naturally have been more receptive lo the peace-and-unity-for-all theme, as this would help them maintain a grip on the country that was shaking perilously.